A 21 Year-Old Male Colorectal Cancer Patient with Clostridium Difficile and Intestinal Amebiasis Infection - LUGITO, NATA PRATAMA HARDJO; -, SUSANTI; KURNIAWAN, ANDREE (Indonesian Journal of Cancer, 2014)
Colorectal cancer is a rare yet aggressive neoplasm in young adult. This cancer was associated with several bacterial and viral infections like Streptococcus bovis, Helicobacter pylori, human papilloma virus, and Clostridium septicum. Here we report a case of Clostridium difficile and Entamoeba histolytica infection in young adult male patient with colorectal cancer. The patient presented with chronic bloody diarrhea since one year prior to diagnosis with histories of antibiotics but no hospitalization, surgery or chemotherapy.